CAD-CAM in the classroom - O'Brien, Bergen; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2003)
This program takes a look at one school that is using Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM) with its students and explores the potential of this technology in contemporary technical education
Title from title screen
Executive producer, Mark McAuliffe ; editor, Michael Henry ; graphics, Michael Henry, Bergen O'Brien ; camera, Kieran Doolan
Keywords: CAD/CAM systems; Computer-aided design